Degradation mechanisms at the Li10GeP2S12/LiCoO2 cathode interface in an all-solid-state lithium-ion battery - Zhang, W; Richter, F; Culver, S; Leichtweiss, T; Lozano, J; Dietrich, C; Bruce, P; Zeier, W; Janek, J (American Chemical Society, 2018)
All-solid-state batteries (ASSBs) show great potential for providing high power and energy density with enhanced battery safety. While new solid electrolytes (SEs) have been developed with high enough ionic conductivities, SSBs with long operational life are still rarely reported. Therefore, on the way to high performance and long-life ASSBs, a better understanding of the complex degradation mechanisms, occurring at the electrode / electrolyte interfaces is pivotal. While the lithium metal / solid electrolyte interface is receiving considerable attention due to the quest for high energy density, the interface between the active material and solid electrolyte particles within the composite cathode is arguably the most difficult to solve and to study. In this work, multiple characterization methods are combined to better understand the processes that occur at the LiCoO2 cathode and the Li10GeP2S12 solid electrolyte interface. Indium and Li4Ti5O12 are used as anode materials to avoid the instability problems associated with Li metal anodes. Capacity fading and increased impedances are observed during longterm cycling. Post-mortem analysis with scanning transmission electron microscopy (STEM), electron energy loss spectroscopy (EELS), x-ray diffraction (XRD) and x-ray photoelectron spectroscopy (XPS) show that electrochemically driven mechanical failure and degradation at the cathode / solid electrolyte interface contribute to the increase in internal resistance and the resulting capacity fading. These results suggest that the development of electrochemically more stable SEs and the engineering of cathode / SE interfaces are crucial for achieving reliable SSB performance.